2020
DOI: 10.1007/s00167-020-06064-8
|View full text |Cite
|
Sign up to set email alerts
|

Autologous protein solution as selective treatment for advanced patellofemoral osteoarthritis in the middle-aged female patient: 54% response rate at 1 year follow-up

Abstract: PurposeThe study wanted to investigate the benefit, durability and safety of autologous protein solution (APS) injection(s) in a middle‐aged female‐only cohort suffering predominantly from patellofemoral osteoarthritis. MethodsFifty females (aged 50.4 ± 6.5) with mainly moderate–severe (86%) patellofemoral cartilage wear (PFCW) were treated with a unilateral intra‐articular APS injection. The KOOS, NRS, Kujala, UCLA and EQ‐5D were assessed at baseline and 1, 3, 6, and 12 months post‐injection. Therapeutic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…[ 32 ] and Van Genechten et al. [ 36 ] showed how PFOA symptoms were recalcitrant to those treatments after 1 year of follow-up, while the present study reported good improvement at a mean follow-up of almost 2 years. On the other hand, Guimaraes et al.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…[ 32 ] and Van Genechten et al. [ 36 ] showed how PFOA symptoms were recalcitrant to those treatments after 1 year of follow-up, while the present study reported good improvement at a mean follow-up of almost 2 years. On the other hand, Guimaraes et al.…”
Section: Discussionsupporting
confidence: 47%
“…Existing literature lacks evidence on the results in patients with isolated primary PFOA treated with autologous microfragmented adipose tissue injection, focusing on results obtained in patients with generic knee OA [ 17 , 28 ]. To our knowledge, only three studies have been previously published on alternative joint-preservation treatments of isolated primary PFOA: the first of these reported the results of concomitant intraarticular injection of MSCs and PRP [ 32 ], the second evaluated the efficacy and safety of autologous protein solution injection [ 36 ], the third evaluated treatment with autologous bone marrow mononuclear cells injection associated with arthroscopic debridement [ 14 ]. However, Pintat et al.…”
Section: Discussionmentioning
confidence: 99%
“…Genechten et al [11] Administration of IA APS led to significant improvement in NPRS, KOOS, and Kujala scores at 12 months' follow-up. Additionally, MRI analysis showed significant improvement in KOOS symptoms and ADL subscales, and Kujala score in patients with major synovitis compared to patients with non-synovitis at 12 months' follow-up.…”
Section: Kon Et Al [10]mentioning
confidence: 97%
“…Additionally, a retrospective study by Kuwasawa et al [ 12 ] conducted in a real-world clinical setting demonstrated that IA injection of APS is safe and efficacious in mild-to-moderate knee OA patients. This study [ 12 ] helped integrate the evidence from real-world populations with differing characteristics with prospective clinical studies [ 7 - 11 ], where the conditions are controlled, thereby improving the wholeness of evidence-based medicine evaluations [ 16 ]. One ongoing clinical trial is registered on the clinical trial protocol repositories (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation